“Um fator seguro de formação adequada”: reformulação curricular na Escola de Educação Física da UFMG (1974-1976) - Jacqueline Fidelis Faria (2019)
This research paper addresses the process of curriculum reformulation that took place at the School of Physical Education at UFMG between 1974 e 1976. The main objective of this research was to understand how this process took place, the factors that influenced its development, as well as its implications for teacher education. The proposed timeframe was between 1974 - the year in which the first curriculum version submitted to the Undergraduate Council was drafted and rejected - and 1976, when the second proposed curriculum was approved. Both the reformulation attempts and the curriculum in force in 1974 were analyzed. We examined how the process of elaboration and re-elaboration of the curriculum reform proposals took place and what changes and immovability could be perceived between the first and the second versions. The priority sources used for the development of this research paper were the documents from the Institutional Funds of the Memory Center of Physical Education, Sport and Leisure (Cemef) of the School of Physical Education at UFMG, such as: different curriculum versions; course syllabus; meeting minute books; as well as the collection of the Undergraduate Council, which belongs to the Administrative Secretary of the Undergraduate Dean's Office. The curriculum which was approved in 1976, published as a book, was also an important source. In the development of this historical research, some assumptions of microhistory were taken as reference, like the reduction and variation of scale. To understand the process of curriculum reformulation that occurred during the military dictatorship, we used the notions of accommodation, conciliation and negotiation strategies. The approved curriculum analysis allowed us to authenticate the establishment of close relations with the sportivization and the search for scientific status, strongly present in the Physical Education field in that period. We also analyzed and discussed the split of curricula by gender and the links with the National Physical Education and Sports Policy.